Konsep Pembiayaan Mudharabah Dalam Perbankan Syariah - Fauzi, Muhammad (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Islam is a comprehensive religion that concretely regulates world affairs and also regulates affairs in the hereafter. One of the teachings of Islam that regulates human life is on the economic aspect (muamalah, iqtishadiyah). Islam in the economic aspect is very large. This study aims to determine the extent to which the concept of mudharabah financing in Islamic banking is discussed in a study. There have been many studies and discussions from previous research on the concept of mudharabah financing in Islamic banking or mudharabahl financing. In this study, mapping of themes from previous studies was carried out through literature studies. From a search on the Google scholar database with the keywords